2021
DOI: 10.1246/bcsj.20200381
|View full text |Cite
|
Sign up to set email alerts
|

Nanographenes from Distinct Carbon Sources

Abstract: This article reports production protocols for nanographenes and the effect of the reaction conditions on their structures and optical properties. These fundamental studies are of value for exploring suitable reaction conditions for the production of nanographenes with desirable properties. Graphite, finely crushed graphite powders, and artificial graphite, all of which are commercially available, are employed. Nanographenes are produced by the acid-assisted oxidative cleavage of the parent carbons followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
0
19
1
Order By: Relevance
“…H 2 SO 4 and 60 % HNO 3 (3 : 1, v/v) at 120 °C for 24 h followed by deionization with dialysis membranes with a pore size of 2 kDa to remove inorganic salts and graphene fragments smaller than the pore size [29, 30] . This procedure was found to produce NGs with a less oxidized surface, [29, 31] as evidenced by a 13 C NMR spectrum of NG‐ 2 in [D 2 ]water, which showed sp 2 carbons and carboxy groups, while oxidized sp 3 carbons on the basal plane were not observed (Figure S11 in the Supporting Information). The size separation of NGs with a dialysis membrane (pore size: 15 kDa) to remove NGs larger than the pore size afforded NG‐ 2 .…”
Section: Figurementioning
confidence: 98%
“…H 2 SO 4 and 60 % HNO 3 (3 : 1, v/v) at 120 °C for 24 h followed by deionization with dialysis membranes with a pore size of 2 kDa to remove inorganic salts and graphene fragments smaller than the pore size [29, 30] . This procedure was found to produce NGs with a less oxidized surface, [29, 31] as evidenced by a 13 C NMR spectrum of NG‐ 2 in [D 2 ]water, which showed sp 2 carbons and carboxy groups, while oxidized sp 3 carbons on the basal plane were not observed (Figure S11 in the Supporting Information). The size separation of NGs with a dialysis membrane (pore size: 15 kDa) to remove NGs larger than the pore size afforded NG‐ 2 .…”
Section: Figurementioning
confidence: 98%
“…[43] The amount of acids and the reaction time affect the PL properties of NGs. [42] The nonstoichiometric mixture of NGs inevitably lowers the reproducibility of their properties, in particular, optical spectra; the optical properties are the sum of those of individual NGs. For example, Matsuda et al reported that the chromatographic separation of NGs yielded NGs with distinct PL properties.…”
Section: Production Of Nanographenesmentioning
confidence: 99%
“…The produced NGs are the mixture of NGs with a few to tens of nanometers and are black to dark blown solids depending on their size distributions [43] . The amount of acids and the reaction time affect the PL properties of NGs [42] …”
Section: Functionalization Of Nanographenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative cleavage of carbon (2 g) with a mixture of concentrated sulfuric acid (60 mL) and nitric acid (20 mL) for 12 h at 120 8C followed by neutralization with Na 2 CO 3 afforded a nanographene mixture (Scheme 1 a). [22] The mixtures were subjected to deionization with dialysis membranes with a pore size of 2 kDa. Nanographenes smaller than the pore size were removed by dialysis.…”
mentioning
confidence: 99%